SCATTERING BY CIRCULAR VOIDS WITH RIGID BOUNDARY: DIRECT AND INVERSE PROBLEMS FOR OPEN AND CLOSE DOMAINS - Rymarczyk, Tomasz; Sikora, Jan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
Problems with the accuracy of calculations by the Boundary Element Method of acoustic and ultrasonic problems formulated in the frequency domain were presented in this paper. The inverse problem was formulated to identify the position and dimensions of the scattering object. A series of numerical experiments carried out with the help of the Boundary Elements Method proved the algorithm’s robustness to noise and high precision in a wide frequency spectrum.